2020
DOI: 10.1073/pnas.2011266118
|View full text |Cite
|
Sign up to set email alerts
|

Prioritized experience replays on a hippocampal predictive map for learning

Abstract: Hippocampal cells are central to spatial and predictive representations, and experience replays by place cells are crucial for learning and memory. Nonetheless, how hippocampal replay patterns dynamically change during the learning process remains to be elucidated. Here, we designed a spatial task in which rats learned a new behavioral trajectory for reward. We found that as rats updated their behavioral strategies for a novel salient location, hippocampal cell ensembles increased theta-sequences and sharp wav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 39 publications
6
74
0
Order By: Relevance
“…Need captures how frequent a given experience will be encountered again in the future, while gain quantifies an expected reward increase from better decisions if that experience is replayed. Consistent with this view, Igata, Ikegaya and Sasaki (28) reported that replay preferentially represents salient locations when rats update their behavioural strategies. Accordingly, we designed a novel decision-making task to measure both the behavioural effect and neural signature of nonlocal learning in humans, while at the same time manipulating need and gain to test its rational prioritisation.…”
Section: Main Textmentioning
confidence: 66%
“…Need captures how frequent a given experience will be encountered again in the future, while gain quantifies an expected reward increase from better decisions if that experience is replayed. Consistent with this view, Igata, Ikegaya and Sasaki (28) reported that replay preferentially represents salient locations when rats update their behavioural strategies. Accordingly, we designed a novel decision-making task to measure both the behavioural effect and neural signature of nonlocal learning in humans, while at the same time manipulating need and gain to test its rational prioritisation.…”
Section: Main Textmentioning
confidence: 66%
“…We found that several pyramidal neurons showed choice-direction selective ( Figures 3A,B ) or reward-direction selective ( Figures 3A,C ) activity. The property of choice-direction cells might be the association between cue tone and choice ( Terada et al, 2017 ) or goal-directed encoding ( Aoki et al, 2019 ; Igata et al, 2021 ). However, the proportion of the choice-direction cells was not learning-dependent and did not significantly differ among the learning stages ( Figure 4D2 ), suggesting that their firing might reflect a stable function in hippocampal CA1 throughout the learning process, such as spatial coding of choice and/or ports.…”
Section: Discussionmentioning
confidence: 99%
“…Replay can also represent experiences that are distant in time and space (Davidson et al, 2009;Karlsson and Frank, 2009), never-used shortcuts between familiar locations (Gupta et al, 2010), and visible but inaccessible places (O ´lafsdo ´ttir et al, 2015). In addition, replay can represent an optimized route through an environment substantially before a subject begins to use the route reliably (Igata et al, 2021). These findings suggest an alternative hypothesis: that rather than informing immediately upcoming behavior, replay instead serves to maintain and link representations of certain places for later use (Dudai, 2012;Girardeau and Zugaro, 2011;Roux et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…During sleep, replay has been linked to memory consolidation, when the repeated activation of hippocampal ensembles is thought to engage plasticity in distributed networks to facilitate long-term memory storage (Dupret et al, 2010;Ego-Stengel and Wilson, 2010;Girardeau et al, 2009;Girardeau and Zugaro, 2011;Gridchyn et al, 2020;Michon et al, 2019;van de Ven et al, 2016). The role of replay during waking is less clear, however: while awake SWRs have been linked to learning (Ferna ´ndez-Ruiz et al, 2019;Igata et al, 2021;Jadhav et al, 2012;Nokia et al, 2012), how the content of those SWRs contributes to memoryrelated information processing remains controversial.…”
Section: Introductionmentioning
confidence: 99%